Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T11:46:35+01:00
A) 2(3-2x)-3 < 3(x-1)-1
6-4x-3 <3x-3-1
-4x+3 < 3x-4
-4x-3x < -4-3
-7x < - 7 |*(-1)
x > 1
b) 2,4(x-1)-4,5 < 3(0,5-0,6x)
2,4x-2,4-4,5 < 1,5-1,8x
2,4x-6,9 < 1,5-1,8x
2,4x+1,8x < 1,5+6,9
4,2x < 8,4 | ÷4,2
x < 2
c) ⅚x - 6+x/₃ ≤ ³/₂ |*3
2½x-18+x ≤ 4½
3½x ≤ 4½+18
3½x≤ 22½
⁷/₂x≤⁴⁵/₂ |*(²/₇)
x≤⁴⁵/₇
x≤ 6 ³/₇
d) 2(x+2)/₃ - (2-3x)/₉ ≥ x-1 |*9
6(x+2) - 2+3x ≥ 9x-9
6x+12 -2+3x≥9x-9
12x+10≥9x-9
12x-9x≥-9-10
3x≥-19 |÷3
x≥ -¹⁹/₃
x≥ -6⅓
e) ⅓(x-½) - 5x-½ ≤ x-⅔(x+1)
⅓x-⅙-5x-½ ≤ x-⅔x-⅔
-4⅔x+⅔x -x ≤ -⅔+⅙+½
-4x-x≤ -⁴/₆+⅙+³/₆
-5x ≤ -³/₆+³/₆
-5x≤0 |÷(-5)
x≥0
148 3 148